(untitled) (Research, Society and Development, 2021)
This research paper aimed to optimize the process parameters and to select the most suitable drying method in order to obtain probiotic powder at reduced cost. The influence of the addition of growth promoters (glucose, sucrose, cheese whey, peptone, yeast extract or ammonium sulfate), incubation parameters (time and temperature) and drying method (freeze-drying or oven-drying) on the viability of the probiotic cultures Lactobacillus casei or Lactobacillus acidophilus was evaluated. The effect of the growth promoters was evaluated using a fractional factorial experimental design 26-4 and the concentration of the growth promoters and the incubation temperature were optimized through Box-Behnken experimental matrix (33). Cheese whey (16% w/v) plus ammonium sulfate (2.5% w/v) and cheese whey (12% w/v) plus yeast extract (7% w/v) promoted a higher multiplication of L. casei and L. acidophilus, respectively. The best temperature for L. casei was 35 ºC and for L. acidophilus 39 ºC, without influence of the incubation time (24 or 48 h). The oven-drying resulted in the highest populations of the probiotic cultures (above 9 log cfu/mL). This study proved that cheese whey can be a suitable growth promoter for both probiotic cultures and oven-drying could be the drying method, which can decrease the production costs. The influence of the temperature and growth promoters is strain specific, demonstrating that the growth conditions should be evaluated for each probiotic strain.